Cash use of the Taiwan Dollar: Is it Efficient? - Philip Hans Franses; Max Welz (Journal of Risk and Financial Management, 2019)
Two banknotes and two coins of the New Taiwan Dollar are infrequently (if at all) used in Taiwan when people make cash payments. This note examines the effect of this behavior on the efficiency of cash payments. The results are compared with the Euro, where the two highest and two lowest tokens are also rarely used. We find for Taiwan that inefficiency increases with 60.7%, while for the Euro it is only 25.3%. The main reason is that two of the rarely used coins and notes in Taiwan are in the middle of the denominational range, whereas for the Euro, these tokens concern the ends of that range.
Keywords: E42; E58; 330; cash payments; efficiency; denomination range